Trends in food safety standards and regulation -- implications for developing countries: food safety in food security and food trade - Caswell, Julie A. (International Food Policy Research Institute, 2003)
Food safety is affected by the decisions of producers, processors, distributors, food service operators, and consumers, as well as by government regulations. In developed countries, the demand for higher levels of food safety has led to the implementation of regulatory programs that address more types of safety-related attributes (such as bovine spongiform encephalopathy (BSE), microbial pathogens, environmental contaminants, and animal drug and pesticide residues) and impose stricter standards for those attributes. They also further prescribe how safety is to be assured and communicated. Liability systems are another form of regulation that affect who bears responsibility when food safety breaks down. These regulatory programs are intended to improve public health by controlling the quality of the domestic food supply and the increasing flow of imported imported food products from countries around the world. -- from Text